Isolation, Characterization, and Safety Evaluation of Human Skin-Derived Precursors from an Adherent Monolayer Culture System - Ru Dai; Wei Hua; Wei Chen; Lidan Xiong; Li Li; Yiming Li (Stem Cells International)
Background. Skin-derived precursors (SKPs) are promising candidates for regenerative medicine. Several studies have transcultured human SKPs (termed tSKPs) from fibroblasts (FBs) expanded in monolayer culture. Herein, we optimized the procedure by treating flasks with poly-2-hydroxyethyl methacrylate (poly-HEMA). Methods. tSKPs generated from our adherent monolayer culture system were investigated for protein expression and differentiation capacity. The aggregated cells and the proliferative cells within tSKP spheres were detected by mix-culturing FBs expressing two different fluorescent proteins and BrdU- or EdU-positive cells, respectively. To distinguish tSKPs from FBs, we compared their phenotypes and transcriptomes. The tumorigenicity of tSKPs and FBs was also assessed in our study. Results. tSKPs expressed Versican, Fibronectin, Vimentin, Sox2, and Nestin. Under appropriate stimuli, tSKPs could differentiate to mesenchymal or neural lineages. While these spheres were heterogeneous populations consisting of both proliferative and aggregated cells, the rate of proliferative cells correlated with a seeding density. tSKPs, isolated from FBs, were distinctive from FBs in cell cycle, marker expression, neural differentiation potential, and transcript profiles despite the two sharing partial similarity in certain properties. As for tumorigenesis, both tSKPs and FBs could be considered as nontumorigenic ex vivo and in vivo. Conclusion. tSKPs were heterogeneous populations presenting similar characteristics as traditional SKPs, while being different from FBs. The potential mixture of FBs in spheres did not affect the biosafety of tSKPs, as both of which had normal karyotype and nontumorigenicity. Taken together, we suggested tSKPs had potential applications in regenerative medicine.